If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x-3)=-8x-24
We move all terms to the left:
8(x-3)-(-8x-24)=0
We multiply parentheses
8x-(-8x-24)-24=0
We get rid of parentheses
8x+8x+24-24=0
We add all the numbers together, and all the variables
16x=0
x=0/16
x=0
| 4x^2+11x−10=4x−2 | | X=2,3x-1= | | 5d-5÷4=2d-3 | | 24a=1920 | | 4/5=t | | (3x+9)•5=45 | | m=3.2 | | 6n=14 | | 20+3x=5(x-10)+3 | | 3x.x=144 | | 20+3=5(x-10)+3 | | F(-3)=8x-5/9x+4 | | 77=5=8n | | 3x+6(2x)=126 | | x–1.89=2.15 | | k-28/5=-15 | | 3+.75x=7+.5x | | -4x-28=2x-48 | | 1.075^n=4 | | 3+.75x=7+.5 | | 2x+8=10x+24 | | 4x^2/45=0 | | 29-y/21=-7 | | 4/7x=3x-51 | | 58v=696 | | 3.7=d-3.8 | | g+4.9=16.15 | | 6–7x=20 | | 7(3+2p+1)=+3(p+1) | | -1/2a-7=-11 | | -6.1x=30.5 | | 3(2x-1)+1x-4=-3 |